Analysis of the original influencing factors and secondary influencing factors of academic papers. Issue 2 (3rd January 2020) - Zhao, Rongying; Bo, Yu
Abstract : Purpose: The influencing factors of academic papers have always been the focus of attention in the field of Scientometrics. Exploring the influencing factors of altmetrics indicators and traditional literature indicators on academic papers is beneficial to better explore the potential significance and value of academic papers in the evaluation of scientific research. The paper aims to discuss these issues. Design/methodology/approach: Based on the latest JCR citation report, this paper selects 22 academic journals in the JIF Quartile Q1 journal of Information Science and Library Science, and then obtains the evaluation data of these journal papers from WOS database and Altmetric.com. This paper uses literature measurement, correlation analysis and regression analysis to explore the influencing factors of the paper. Findings: The results show that the original influencing factors of academic papers have a significant impact on secondary influencing factors. What is more obvious is that the number of references (nr) presents a significant positive correlation with the total number of times (Z9), the number of uses (U1) and (U2). Originality/value: This paper combines traditional literature indicators with Altmetrics indicators to study the influencing factors through primary influencing factors and secondary influencing factors. Through research, it denies the phenomenon that academic circles have published academic papers in the world in recent years to overemphasize certain factors to improve the influence of the paper.